PENGARUH PENGGUNAAN FINANCIAL TECHNOLOGY (E-WALLET) DAN GAYA HIDUP TERHADAP PERILAKU PENGELOLAAN UANG MAHASISWA - Dinda Dwi Aprillia; Narach Larasati Nasution; Anggie Pricyla Sianturi; Nur Azizaini Zhaharah; Imelda Malona Traigan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the effect of financial technology in the form of e-wallet usage and lifestyle on students’ financial management behavior. The research employed a quantitative approach using a questionnaire distributed to 50 students of the Faculty of Economics, Universitas Negeri Medan, selected through purposive sampling. Data were analyzed using multiple linear regression after conducting validity, reliability, and classical assumption tests. The results indicate that both e-wallet usage and lifestyle have no significant effect on students’ financial management behavior. These findings suggest that internal factors such as financial literacy, self-control, and personal experience play a more dominant role in shaping financial behavior than external factors. The study contributes theoretically to the discussion of personal financial management and provides practical implications emphasizing the importance of financial education for students to manage their finances wisely.